HPLC for simultaneous quantification of free mannose and glucose concentrations in serum: use in detection of ovarian cancer - Chen, Yulong; Yao, Qin; Zhang, Lijuan; Zeng, Pengjiao (Frontiers in Chemistry, 2023)
Background: Abnormal levels of monosaccharides in blood have been linked to tumorigenesis. In this study, a novel high-performance liquid chromatography (HPLC) method was established for the simultaneous determination of free mannose and glucose in the serum. Methods: The serum was directly derivatized by 1-phenyl-3-methyl-5-pyrazolone under alkaline conditions using L-rhamnose as an internal standard. The chromatographic separation was then performed on a Poroshell EC-C18 chromatographic column (4.6 × 100 mm, particle size 2.7 μm, Agilent) with gradient elution using NH4Ac-HAc and acetonitrile as the mobile phases. The method was thereafter validated according to international guidelines. The serum samples obtained from 200 healthy individuals and 200 ovarian cancer (OC) patients were analyzed for free mannose and glucose. Results: The method was found to be reproducible for quantification within 20 min and included online sample purification. The method displayed excellent linearity in the concentration range (for mannose: 0.5–500 μg/mL; glucose: 0.5–1500 μg/mL). The precision, recovery, and stability met the FDA bioanalytical method validation acceptance criteria. Overall, the measurement of glucose content by HPLC correlated well with the different enzymatic methods. Ovarian cancer mannose levels in the serum were significantly higher in the advanced stage (61.22 μmol/L, p < 0.0001) than those in healthy volunteers and early-stage patients (44.51 μmol/L versus 50.09 μmol/L, p < 0.0001). The AUC for the ratio of serum free glucose to mannose (G/M) was 0.98 (p < 0.0001), with a sensitivity of 91.46% and a specificity of 98.50%, which served as a biomarker for OC diagnosis. Conclusion: We report a simple, repeatable, and attractive analytical method by HPLC, which can be used for quantitative estimation of free mannose and glucose simultaneously in human serum. Our results indicate that the serum level of mannose could be used as a potential biomarker of ovarian cancer.